Current Knowledge of Asthma-COPD Overlap (ACO) Genetic Risk Factors, Characteristics, and Prognosis. (16th September 2021) - Odimba, Ugochukwu; Senthilselvan, Ambikaipakan; Farrell, Jamie; Gao, Zhiwei
Abstract: Asthma-COPD overlap (ACO) is a newly identified phenotype of chronic obstructive airway diseases with shared asthma and COPD features. Patients with ACO are poorly defined, and some evidence suggests that they have worse health outcomes and greater disease burden than patients with COPD or asthma. Generally, there is no evidence-based and universal definition for ACO; several consensus documents have provided various descriptions of the phenotype. In addition, the mechanisms underlying the development of ACO are not fully understood. Whether ACO is a distinct clinical entity with its particular discrete genetic determinant different from asthma and COPD alone or an intermediate phenotype with overlapping genetic markers within asthma and COPD spectrum of obstructive airway disease remains unproven. This review summarizes the current knowledge of the genetic risk factors, characteristics, and prognosis of ACO.